NON-DESCENT VAGINAL HYSTERECTOMY USING BIPOLAR VESSEL SEALING SYSTEM VERSUS TOTAL LAPAROSCOPIC HYSTERECTOMY FOR BENIGN DISEASES OF UTERUS: A PROSPECTIVE INTERVENTIONAL STUDY - SINGH, SUNDER PAL; MANGLA, DIVYA; KUMAR, VIPIN (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study was to compare the surgical outcomes of non-descent vaginal hysterectomy (NDVH) using bipolar vessel sealing system and total laparoscopic hysterectomy (TLH) with reference to intraoperative time, intraoperative blood loss, and post-operative pain. Methods: The study was conducted on 100 patients who required hysterectomy for benign diseases of uterus and was fit to undergo both modalities of surgery (TLH/NDVH). 50 patients that underwent TLH and 50 patients that underwent NDVH with BipBIPVSS were part of Study Group. Results: The mean intraoperative time taken in performing NDVH using Bipolar BIPVSS (28.06 min) was significantly less than the mean time taken in performing TLH (92.62 min). The intraoperative blood loss in NDVH with BIPVSS was 41.70 mL and TLH was 89.24 mL. The post-operative pain in both the study group was not statistically significant as both the groups had similar experience and p>0.05. Post-operative major complication of bleeding in ovarian artery and hemoperitoneum was observed in a patient of NDVH with BIPVSS while one case of thermal rectal injury and one case of bladder injury were observed in TLH group. Conclusion: The route and procedure of hysterectomy will depend on various factors; however, NDVH with BIPVSS has certain advantage over TLH as it takes lesser times, lesser blood loss and gives similar pain experience if not better than TLH.